Preparation of Bioactive Titanium Surfaces via Fluoride and Fibronectin Retention - Elias, Carlos Nelson; Gravina, Patricia Abdo; Silva Filho, Costa e; Nascente, Pedro Augusto de Paula (International Journal of Biomaterials, 2012)
Statement of Problem. The chemical or topographic modification of the dental implant surface can affect bone healing, promote accelerated osteogenesis, and increase bone-implant contact and bonding strength. Objective. In this work, the effects of dental implant surface treatment and fibronectin adsorption on the adhesion of osteoblasts were analyzed. Materials and Methods. Two titanium dental implants (Porous-acid etching and PorousNano-acid etching followed by fluoride ion modification) were characterized by high-resolution scanning electron microscopy, atomic force microscopy, and X-ray diffraction before and after the incorporation of human plasma fibronectin (FN). The objective was to investigate the biofunctionalization of these surfaces and examine their effects on the interaction with osteoblastic cells. Results. The evaluation techniques used showed that the Porous and PorousNano implants have similar microstructural characteristics. Spectrophotometry demonstrated similar levels of fibronectin adsorption on both surfaces (80%). The association indexes of osteoblastic cells in FN-treated samples were significantly higher than those in samples without FN. The radioactivity values associated with the same samples, expressed as counts per minute (cpm), suggested that FN incorporation is an important determinant of the in vitro cytocompatibility of the surfaces. Conclusion. The preparation of bioactive titanium surfaces via fluoride and FN retention proved to be a useful treatment to optimize and to accelerate the osseointegration process for dental implants.